1982
DOI: 10.1037/0022-3514.43.6.1254
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation, moderator variables, and the validity of personality tests: A peer-rating study.

Abstract: A study with 85 college fraternity members investigated the effects of aggregation and moderator variables on the validity of personality tests. Aggregation over items and raters yielded an average self–peer correlation of .44 for ratings on 4 personality dimensions. The combination of social communication skill and self-knowledge produced significant moderating effects. Ss high on the Acting subscale and high on a composite of Private Self-Consciousness and Personal Identity scales had stronger agreement betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
184
2
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(212 citation statements)
references
References 65 publications
25
184
2
1
Order By: Relevance
“…At the same time as findings consistent with the self-monitoring formulation have accumulated, there clearly have been some failures to confirm hypotheses derived from the self-monitoring construct (e.g., Arkin, Gabrenya, Appelman, & Cochran, 1979;Cheek, 1982;Santee & Maslach, 1982;Schneiderman, 1980;Wolfe, Lennox, & Hudiburg, 1983;Zanna et al, 1980;Zuckerman & Reis, 1978). Of course, given the known effects of sampling variability, occasional failures to confirm hypotheses in specific samples must be expected even when genuine effects exist in the general population.…”
Section: Self-monitoring: Validity Of the Interpretationmentioning
confidence: 99%
“…At the same time as findings consistent with the self-monitoring formulation have accumulated, there clearly have been some failures to confirm hypotheses derived from the self-monitoring construct (e.g., Arkin, Gabrenya, Appelman, & Cochran, 1979;Cheek, 1982;Santee & Maslach, 1982;Schneiderman, 1980;Wolfe, Lennox, & Hudiburg, 1983;Zanna et al, 1980;Zuckerman & Reis, 1978). Of course, given the known effects of sampling variability, occasional failures to confirm hypotheses in specific samples must be expected even when genuine effects exist in the general population.…”
Section: Self-monitoring: Validity Of the Interpretationmentioning
confidence: 99%
“…This seemed necessary because of the impression of almost universal inaccuracy that some readers derived from research on error. In this phase, investigators reported studies showing how personality traits affect behavior and how laypersons can make judgments of such traits that manifest both interjudge agreement and predictive validity (e.g., Cheek, 1982;Funder, 1980aFunder, , 1980bFunder, , 1982Kenrick & Stringfield, 1980;Moskowitz & Schwarz, 1982). These two kinds of criteria-agreement and behavioral prediction-became the basis of accuracy research that followed over the next decade (Funder, 1987;Hinder & West, 1993a).…”
Section: The Development Of Research On Accuracymentioning
confidence: 99%
“…An examination of criteria besides self-reports would add considerably to our knowledge concerning the accuracy of interpersonal perception, especially because self-report data are likely to be biased (Cheek, 1982;Kagan, 1988;Wiggins, 1973). Of particular value would be any evidence regarding the relationship between strangers' judgments of targets observed in a naturalistic situation and a criterion variable characterized by both pragmatic utility and ecological validity -one that is used in everyday decisions about people.…”
Section: Ecologically Valid Criterion Variablementioning
confidence: 99%